2008
DOI: 10.1111/j.1740-0929.2008.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the rearing system on the quality traits of the carcass, meat and fat of the Chato Murciano pig

Abstract: To evaluate the performance of the Spanish autochthonous pig breed Chato Murciano under different rearing conditions, a total of 30 castrated male pigs were used. Eighteen pigs were reared in an outdoor system, and sent to slaughter with an average age of 210 days and live weight (LW) of 124.41 kg; and 12 pigs were reared in an indoor system, and slaughtered with 119.58 kg of LW and 236 days old. The pigs reared outdoors showed a better growing rate and final live weight in relation to age, as well as higher h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
12
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
7
12
0
1
Order By: Relevance
“…Fernandez et al (1999) indicated that levels over 3.5 % are associated with a significant risk of meat being rejected by consumers (referring to fresh meat). Results for IMF obtained in the present study for Pulawska pigs are in agreement with investigations performed on autochthonous pigs by Galián et al (2008) and Yu et al (2013). In the study of Poto et al (2007) (2010), who reported that the mean fat content in loin of Polish Landrace pigs was 1.76 %.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Fernandez et al (1999) indicated that levels over 3.5 % are associated with a significant risk of meat being rejected by consumers (referring to fresh meat). Results for IMF obtained in the present study for Pulawska pigs are in agreement with investigations performed on autochthonous pigs by Galián et al (2008) and Yu et al (2013). In the study of Poto et al (2007) (2010), who reported that the mean fat content in loin of Polish Landrace pigs was 1.76 %.…”
Section: Discussionsupporting
confidence: 81%
“…An abnormally rapid rate of post-mortem glycolysis (initial pH ≤ 6.0) in the muscles produces poor-quality pork (pale, soft and exudative meat) (Galián et al, 2008). In our study the percent drip loss of pork decreases along with increasing pH.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations